INOVASI LAYANAN PERPUSTAKAAN BERBASIS INKLUSI SOSIAL DI DINAS KEARSIPAN DAN PERPUSTAKAAN KABUPATEN KEBUMEN - Sundariyati, Dwi (Institut Agama Islam Negeri Salatiga, 2024)
Social society inclusion is a process of developing the capacity of individuals and groups to participate and play a role. This research aims to discover the innovation model and development of library services based on social inclusion. And obstacles faced in the implementation of the development of the innovation. This research method uses a descriptive qualitative approach, data collection techniques observation, and in-depth interviews. The data validity test with the triangulation test is through the collection of data from the results of interviews and observations that have been made. The formulation of the problem that the author will examine is how service innovation is based on social inclusion at the Kebumen Regency Regional Archives and Library Office. The results showed that the Kebumen Regency Regional Archives and Library Service innovated library services based on social inclusion, for the innovations, namely Lampborgini services, namely the latest generation mobile car services, craft academy services, namely applicative activities by involving the community in workshop activities with topics according to books in the library, kupu- kupu malam service, namely mandatory visiting activities for kindergarten, elementary, junior high school children filled with various activities according to their talents and interests, cheerful library tourism movement services, smart services, community fair services, Jurassicpark services, rational services (literacy on alun-alun). Factors that support library activities in social inclusion-based library service innovation are budget, human resources, and technological developments. The obstacles are community, budget, and human resources